Aerodynamic analysis during the in-run phase of ski jumping: A numerical study of body posture effects - Li, W.; Chen, L.; Zhao, T.; Xu, G.; Li, Q.; Shi, W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The performance of ski jumping has a strong correlation to the in-run speed at take-off, which is underpinned by multi-disciplinary principles. Conventional research on the aerodynamics of ski jumping is supported by wind tunnels while the fluid physics leading to the performance is underexplored. Using computational fluid dynamics (CFD) methods, the aerodynamic drag, and its underlying flow patterns of seven typical in-run postures of a national-team athlete are investigated. The athlete model, including the suits and gear, are constructed through three-dimensional (3D) scanning. An optimal posture is proposed for this specific athlete to minimize the aerodynamic drag during the in-run. The critical adjustment of the posture is to spread the forearms and hands into a straight position. The effects of in-run speed on the aerodynamic drag production are related to the evolution of vortical structures around the athlete. This research encourages the usage of the CFD method in determining the optimal posture of ski jumping (during both in-run and flight phases) and thus serves as another critical technique in training. Our results also infer that the optimal posture should be customized for each athlete according to their biological features and training background.